2011
DOI: 10.3354/meps08965
|View full text |Cite
|
Sign up to set email alerts
|

Bryozoan growth and environmental reconstruction by zooid size variation

Abstract: The modular growth of cheilostome bryozoans combined with temperature-induced variation in module (zooid) size has enabled the development of a unique proxy for deducing seasonal temperature regimes. The approach is based on measures of intracolonial variation in zooid size that can be used to infer the mean annual range of temperature (MART) experienced by a bryozoan colony as predicted by a model of this relationship that was developed primarily to infer palaeoseasonal regimes. Using the model predictions ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…For colonial animals like bryozoans, the relationship is expressed at the zooid level, and there is a reasonable body of evidence that zooid size is indeed inversely related to temperature. This evidence comes from diverse laboratory-reared material (e.g., Menon 1972, Hunter and Hughes 1994, Atkinson et al 2006, Amui-Vedel et al 2007, O'Dea et al 2007b, diverse field-collected material (e.g., Okamura 1987, O'Dea and Okamura 2000b, 2000c, O'Dea and Jackson 2002, O'Dea 2005, Lombardi et al 2006, and the growth of bryozoans in the field (O'Dea and Okamura 1999; see Okamura et al 2011 for further review) There are other factors that influence the ultimate size of zooids, the most obvious being species-specific colonial growth rules, such as the production of annual growth check lines (O'Dea andOkamura 2000b, O'Dea 2005, Okamura et al unpubl data), substrate irregularities, predation, and competition from other sessile encrusters, the influence of which can be minimized with the judicious rejection of randomly selected zooids as the approach requires (O'Dea andOkamura 2000a, O'Dea 2005). Salinity and food availability (Hageman et al 2009) have also been shown to influence zooid size, yet the effects are minimal in comparison with those of temperature (Okamura 1987, Hunter and Hughes 1994, O'Dea and Okamura 1999, 2000b, O'Dea 2005, O'Dea et al 2007b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For colonial animals like bryozoans, the relationship is expressed at the zooid level, and there is a reasonable body of evidence that zooid size is indeed inversely related to temperature. This evidence comes from diverse laboratory-reared material (e.g., Menon 1972, Hunter and Hughes 1994, Atkinson et al 2006, Amui-Vedel et al 2007, O'Dea et al 2007b, diverse field-collected material (e.g., Okamura 1987, O'Dea and Okamura 2000b, 2000c, O'Dea and Jackson 2002, O'Dea 2005, Lombardi et al 2006, and the growth of bryozoans in the field (O'Dea and Okamura 1999; see Okamura et al 2011 for further review) There are other factors that influence the ultimate size of zooids, the most obvious being species-specific colonial growth rules, such as the production of annual growth check lines (O'Dea andOkamura 2000b, O'Dea 2005, Okamura et al unpubl data), substrate irregularities, predation, and competition from other sessile encrusters, the influence of which can be minimized with the judicious rejection of randomly selected zooids as the approach requires (O'Dea andOkamura 2000a, O'Dea 2005). Salinity and food availability (Hageman et al 2009) have also been shown to influence zooid size, yet the effects are minimal in comparison with those of temperature (Okamura 1987, Hunter and Hughes 1994, O'Dea and Okamura 1999, 2000b, O'Dea 2005, O'Dea et al 2007b.…”
Section: Methodsmentioning
confidence: 99%
“…Although the mechanistic basis is subject to debate (see Okamura et al 2011 for review), the generality of this inverse relationship enables a means of inferring temperatures based on body size. For colonial animals like bryozoans, the relationship is expressed at the zooid level, and there is a reasonable body of evidence that zooid size is indeed inversely related to temperature.…”
Section: Methodsmentioning
confidence: 99%
“…For example, according to Hughes & Jackson (1990) and Kuklinski & Taylor (2008), avicularia, generally regarded as having a defensive role, are smaller and fewer in number in high latitude congeneric species, suggesting that predator pressure is relatively less important than physical stresses in these environments. In addition, there is an inverse intraspecific relationship between the size of the zooids in living cheilostome bryozoan colonies and the ambient temperature at the time of budding (see Okamura et al 2011). Limited evidence suggests that this relationship is also true between congeneric species: Kuklinski & Taylor (2008) found that the size of the autozooecia in cheilostome species belonging to six of the eight genera they studied was significantly greater in the Arctic than in congeneric species from lower latitude, warmer water sites.…”
mentioning
confidence: 98%
“…Achieving reliable estimates of MART requires strict adherence to several rules described in O'Dea and Okamura (2000b) and Okamura et al (2011). These aim to minimize the known effects of water current activity (Okamura and Partridge, 1999;Berning, 2007) …”
Section: Approach 1: Zooid-size Approach To Martmentioning
confidence: 99%